Polymerization methods and characterizations for Poly(Lactic Acid) (PLA) based polymers - Ali, Fathilah; Ismail, Norshafiq (Springer Nature, 2018)
Polymers based from petrochemical have been widely used in various applications due to their availability and lower cost. Products produced from petrochemicals have excellent properties. However their low biodegradability rate had caused terrible environmental problems. Therefore, polymers based on natural resources such as natural polymers, biopolymers, and synthetic polymers are highly in demand as they can be produced from natural sources which means they are sustainable. Apart of that, due to their nature, they are environmentally friendly and biodegradable. There are many types of biopolymers such as cellulose, poly(lactic acid) (PLA), polyhydroxybutyrate (PHB) and much more. Among these biopolymers, PLA has high potential because it has similar properties to conventional polymers such as polystyrene (PS). This polymer is an aliphatic type polyester which can be polymerized from its’ monomer, lactic acid. Lactic acid (LA) can be obtained from the fermentation process of natural sources such as starch (Auras R, Harte B, Selke S; Macromol Biosci 4(9):835–864, 2004).